Introduction - García Gimenez, Antonio; Pérez Tornero, José Manuel (Anàlisi, 2013)
This special issue of Anàlisi presents progresses and developments in the broad field of media literacy of young people. It points out the issues that seem crucial at the moment and it does in a international perspective that combines a comparative look, in some cases, with the local study —especially on issues affecting Europe and Spain. It shows the interest of the researchers in this field and, at the same time, the gradual integration and consolidation of methodologies and shared points of view being experienced in this field in recent times.